Prevalence of low testosterone in aging men with benign prostatic hyperplasia: data from the Proscar Long-term Efficacy and Safety Study (PLESS). (June 2013) - Kaplan, Steven A.; O'Neill, Edward; Lowe, Robert; Hanson, Mary; Meehan, Alan G.
Abstract Objectives: We examined the prevalence of low testosterone (LT) in the subset of men in the Proscar Long-term Efficacy and Safety Study (PLESS) who had serum total testosterone (TT) measured at baseline. Methods: PLESS enrolled 3040 men with benign prostatic hyperplasia (BPH). Of these men, 299 had TT and body mass index (BMI) measurements at baseline. Patients were classified as having LT if their baseline TT was <300 ng/dl. Results: Of the 299 PLESS patients with baseline TT and BMI measurements, 65 (21.7%) had LT. The prevalence of LT increased with increasing BMI, occurring in 8/78 (10.3%) normal weight patients (baseline BMI <25 kg/m2), 35/160 (21.9%) overweight patients (baseline BMI ≥25–<30 kg/m2), and 22/61 (36.1%) obese patients (baseline BMI ≥30 kg/m2). Conclusions: LT was observed in more than one in five PLESS patients with baseline TT and BMI measurements. The prevalence of LT increased with increasing BMI – more than one in three obese PLESS patients with baseline TT measurements had LT.